Tax Responsibility of Banks for Non-Execution of Tax Authorities’ Decisions: Legislative Regulation and Law Enforcement Practice - BOCHKAREVA, Ekaterina Alexandrovna; KOZHUSHKO, Svetlana Valerievna; KHAMIDULLIN, Kamil Shamilievich; FARIKOVA, Ekaterina Alexandrovna (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research issue is to identify the shortcomings of legal management of tax responsibility of banks in case of their non-execution of tax authorities’ decisions, as well as to define the possible directions of improvement of legislation and law enforcement practice in this sphere. The aims and objectives of the research are as follows: (1) to analyze the provisions of Article 134 and Article 135 of the Tax Code of the Russian Federation, which establish the responsibility of banking organizations as participants of the fiscal relations and to analyze the application of provisions of these articles by judicial and tax authorities; (2) to identify the problems of bringing to responsibility credit banking organizations for their non-execution of tax authorities’ decisions; (3) to develop recommendations for improvement of legal regulation. The methods of the research include analysis, analogy, legalistic method and integrated interpretation. The results of the research are as follows. It has been justified that the sum of debt of a taxpayer, established to bring banks to legal responsibility under Article 134 of the Tax Code of the Russian Federation, shall not include the sums of fines and penalties, as the bank is not a real participant of legal relations ‘tax authority – taxpayer’ and is deprived of the right to appeal the sum, which serves as the basis for establishing the sum of fine.